Brief Considerations Regarding the Concept of Rule of Law in the Context of the Covid-19 Global Crisis - Matic, Andreea Elena; Agheniței, Mihaela (Acta Universitatis Danubius. Juridica, 2022)
In the present paper we aim to analyse some aspects in which the COVID-19 pandemic generated a crisis regarding the application of the rule of law. First, we will refer to some general aspects regarding the content and importance of rule of law concept in democratic societies. Then, taking into account the fact that the law regulates situations that occur in real life, in society, we will discuss the fact that the COVIC 19 pandemic situation generated circumstances which had not been foreseen by the democratic states authorities and this generated an actual global crisis. This crisis affected the rules regarding the good governance. As the pandemic is approaching its end, our societies are not yet prepared to enforce new necessary aspects of the rule of law. Also, we will refer to the fact that the year 2021 was the third year in a row in which WJP Rule of Law® reported that the rule of law scores of several countries have declined rather than improved.